Sharia Economic Law Regulation In Indonesia And Malaysia: Implementation And Challenges - Khotimah, Umi Khusnul (Faculty of Law, Universitas Pattimura, 2024)
Introduction: This article explores the implementation and regulatory challenges of Sharia economic law in Indonesia and Malaysia, two key players in Islamic finance. Both countries have integrated Islamic principles into their economic frameworks, but their approaches differ due to legal, historical, and political factors.Purposes of the Research: The purpose of this article is to analyze and compare the regulatory frameworks governing Sharia economic law in Indonesia and Malaysia. It aims to highlight both the successes and obstacles in implementation, while offering potential recommendations for improvement.Methods of the Research: This study employs a comparative legal research methodology, analyzing primary legal sources such as laws, regulations, and official guidelines from Indonesia and Malaysia. Secondary sources, including academic articles and government publications, provide context for understanding how these frameworks are implemented.Results of the Research: The research finds that Malaysia’s centralized regulatory system, led by the Sharia Advisory Council (SAC), provides clear guidelines for Sharia-compliant financial products. In contrast, Indonesia’s regulatory framework is more fragmented, with overlapping responsibilities between institutions, creating challenges for effective implementation.